2015
DOI: 10.1038/nature14953
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of an active lipid-linked oligosaccharide flippase

Abstract: The flipping of membrane-embedded lipids containing large, polar head groups is slow and energetically unfavourable, and is therefore catalysed by flippases, the mechanisms of which are unknown. A prominent example of a flipping reaction is the translocation of lipid-linked oligosaccharides that serve as donors in N-linked protein glycosylation. In Campylobacter jejuni, this process is catalysed by the ABC transporter PglK. Here we present a mechanism of PglK-catalysed lipid-linked oligosaccharide flipping bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
221
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(235 citation statements)
references
References 62 publications
11
221
3
Order By: Relevance
“…The crystal structures of exporters display varying degrees of NBD disengagement in the absence of nucleotides (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). These data were questioned as a detergent artifact mistaken for dynamic NBDs.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 4 more Smart Citations
“…The crystal structures of exporters display varying degrees of NBD disengagement in the absence of nucleotides (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). These data were questioned as a detergent artifact mistaken for dynamic NBDs.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…DEER data of ABC transporters in liposomes and bicelles show broad lines for apo NBDs (Dong et al , 2005; Borbat et al , 2007; Zou et al , 2009; Bountra et al , 2017), further suggesting that in the absence of nucleotides the NBDs can have different degrees of disengagement. Upon nucleotide binding, the NBDs dimerize and display nearly identical distances across different transporters (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). Our smFRET data in detergent and liposomes revealed that the NBDs of McjD adopt very similar disengagement with E* values of 0.3 and larger E* values of 0.5 upon nucleotide binding.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations